1992
DOI: 10.1042/bj2860289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyrazole, cobalt and phenobarbital on mouse liver cytochrome P-450 2a-4/5 (Cyp2a-4/5) expression

Abstract: Pyrazole, cobalt and phenobarbital increase the activity of coumarin 7-hydroxylase (COH) in mouse liver. To study the mechanism of this increase, we measured the expression of the cytochrome P-450 2a-4/5 (Cyp2a-4/5) complex, which mediates testosterone 15 alpha-hydroxylase and COH activities, as a function of dose and time after the treatment of C57BL/6 (B6) and DBA/2 (D2) male mice with the inducers. COH activity and Cyp2a-4/5 steady-state mRNA levels were increased in both strains in response to the inducers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 38 publications
(36 reference statements)
1
31
1
Order By: Relevance
“…The posttranscriptional regulation of Cyp2a5 identified to date, include mRNA stabilization and protein stabilization to increase expression and activity. The evidence of Cyp2a5 mRNA stabilization was first reported by Aida and Negishi (Aida and Negishi, 1991;Hahnemann et al, 1992). Heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), a multifunctional protein involved in transcriptional regulation and cell growth, has been identified as the RNA-binding protein responsible for the Cyp2a5 mRNA stabilization (Tilloy-ellul et al, 1999;Raffalli-Mathieu et al, 2002).…”
Section: Post-transcriptional Regulation Of Cyp2a5mentioning
confidence: 99%
See 2 more Smart Citations
“…The posttranscriptional regulation of Cyp2a5 identified to date, include mRNA stabilization and protein stabilization to increase expression and activity. The evidence of Cyp2a5 mRNA stabilization was first reported by Aida and Negishi (Aida and Negishi, 1991;Hahnemann et al, 1992). Heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), a multifunctional protein involved in transcriptional regulation and cell growth, has been identified as the RNA-binding protein responsible for the Cyp2a5 mRNA stabilization (Tilloy-ellul et al, 1999;Raffalli-Mathieu et al, 2002).…”
Section: Post-transcriptional Regulation Of Cyp2a5mentioning
confidence: 99%
“…Furthermore, these conditions appear to be associated with increased serum bilirubin levels (Bonacini, 2004;Malaguarnera et al, 2005;Richardson et al, 2006b;Hansen, 2010). (Pellinen et al, 1993) Chloroform Anesthetic/Teflon (Camus et al, 1996) Cocaine Topical anesthetic (Pellinen et al, 1994a(Pellinen et al, , 1994b) Ethanol Fuel, beverage, and antiseptic (Lu et al, 2010) Phenobarbital Barbiturate and anticonvulsant (Hahnemann et al, 1992;Salonpää et al, 1994) Pyrazole Precursor for various medicines (Juvonen et al, 1985;Nichols and Kirby, 2008 (Cai et al, 2002) Buthionine sulfoximine Drug used in chemotherapy to reduce levels of glutathione (Gilmore et al, 2003) pregnenolone 16a-carbonitrile (PCN) Pregnane X receptor (PXR) agonist or antiglucocorticoid (Cai et al, 2002) Rifampicin Bactericidal antibiotics (Donato et al, 2000) Trans-4,5-dihydroxy-1,2-dithiane (DTTox) Intramolecular disulfide form of dithiothreitol; reducing agent (Gilmore and Kirby, 2004) (Montero et al, 1999) Bilirubin Bilirubin (BR) is the end product of heme catabolism, and heme is found in hemoglobin or other hemoproteins such as cytochromes, catalase, and a small pool of unbound free heme (Roy-Chowdhury et al, 2007). BR consists of a tetrapyrrole ( Figure D1).…”
Section: Pathophysiological States Associated With Cyp2a5mentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome P450 2a5 (CYP2A5) is induced by a diverse array of hepatotoxins, including nitrogen heterocycles (Kojo et al, 1998), chlorinated hydrocarbons (Camus-Randon et al, 1996), metal ions (Hahnemann et al, 1992), and porphyrinogenic agents (Donato et al, 2000), which are neither structurally similar nor generally considered to be inducers of P450s. Moreover, CYP2A5 is induced during viral (Kirby et al, 1994a), fulminant (Chemin et al, 1996), bacterial (Sipowicz et al, 1997), and parasitic hepatitis (Kirby et al, 1994b), pathophysiological conditions that are usually associated with suppression of P450s.…”
mentioning
confidence: 99%
“…19) In the case of mouse, coumarin is 7-hydroxylated by CYP2A5. 20) During the course of investigation of the mechanism of selenocysteine synthesis with cytosol from bovine liver, 21) we reserved a large amount of bovine liver microsomes and found that bovine liver microsomes had the ability to catalyze coumarin to 7-hydroxycoumarin, which is generally dependent on CYP2A6 in human. We have also studied quinoline metabolism by the phase I reaction.…”
Section: -5)mentioning
confidence: 99%